A Case Report of Prilocaine-Induced Methemoglobinemia after Liposuction Procedure. (23rd June 2015) - Yildirim, Birdal; Karagoz, Ulku; Acar, Ethem; Beydilli, Halil; Nese Yeniceri, Emine; Tanriverdi, Ozgur; Alatas, Omer Dogan; Kasap, Şükrü
Abstract : Prilocaine-induced methemoglobinemia is a rarely seen condition. In this paper, a case is presented with methemoglobinemia developed secondary to prilocaine use in a liposuction procedure, and the importance of this rarely seen condition is emphasized. A 20-year-old female patient presented with complaints of prostration, lassitude, shivering, shortness of breath, and cyanosis. It was learned that the patient underwent nearly 1000 mg prilocaine infiltration 8 hours priorly during a liposuction procedure. At admission, her blood pressure (130/80 mmHg), pulse rate (140 bpm), body temperature (36°C), and respiratory rate (40/min) were recorded. The patient had marked acrocyanosis. The arterial blood gas methemoglobin level was measured as 40%. The patient received oxygen therapy with a mask and was administered vitamin C in normal saline (500 mg tid), N-acetylcysteine (300 mg tid), and 50 mg 10% methylene blue in the intensive care unit of the internal medicine department. Methemoglobin level dropped down to 2% after her treatment with methylene blue and she was clinically cured and discharged 2 days later. Emergency service physicians should remember to consider methemoglobinemia when making a differential diagnosis between dyspnea and cyanosis developing after prilocaine infiltration performed for liposuctions in the adult age group.